2018
DOI: 10.1371/journal.pone.0201848
|View full text |Cite
|
Sign up to set email alerts
|

Strain differences in thymic atrophy in rats immunized for EAE correlate with the clinical outcome of immunization

Abstract: An accumulating body of evidence suggests that development of autoimmune pathologies leads to thymic dysfunction and changes in peripheral T-cell compartment, which, in turn, perpetuate their pathogenesis. To test this hypothesis, thymocyte differentiation/maturation in rats susceptible (Dark Agouti, DA) and relatively resistant (Albino Oxford, AO) to experimental autoimmune encephalomyelitis (EAE) induction was examined. Irrespective of strain, immunization for EAE (i) increased the circulating levels of IL-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 97 publications
(162 reference statements)
1
15
0
Order By: Relevance
“…Of interest, altered thymic activity had already been suggested in relapse-remitting MS patients ( 23 ) and thymic atrophy was also found in other MS models, namely the cuprizone model ( 38 ), in A.SW mice with primary-progressive EAE ( 39 ) and also, recently, in rat EAE models ( 40 ). Herein we also showed thymic atrophy accompanied by decreased percentage of viable cells, that could result from apoptotic cell death, as observed in the rat EAE models ( 40 ).…”
Section: Discussionmentioning
confidence: 94%
“…Of interest, altered thymic activity had already been suggested in relapse-remitting MS patients ( 23 ) and thymic atrophy was also found in other MS models, namely the cuprizone model ( 38 ), in A.SW mice with primary-progressive EAE ( 39 ) and also, recently, in rat EAE models ( 40 ). Herein we also showed thymic atrophy accompanied by decreased percentage of viable cells, that could result from apoptotic cell death, as observed in the rat EAE models ( 40 ).…”
Section: Discussionmentioning
confidence: 94%
“…However, the loss of CD28 could also be ascribed, apart from repeated TCR activation, to enhanced action of proinflammatory cytokines (TNF-α and IL-6) [248]. Accordingly, CD4+CD28-T cells are shown to accumulate with development of chronic inflammatory autoimmune diseases, including MS and EAE [45,241,242,249,250]. Our data showed that CD4+CD28-T cell accumulation in EAE rats could also be ascribed to thymic atrophy evoked by the increased blood levels of the proinflammatory cytokines [45].…”
Section: Influence Of Aging On Tconsmentioning
confidence: 66%
“…To add to complexity of thymic involution are data indicating that, in both humans and experimental animals, development of chronic inflammatory autoimmune diseases, including MS/EAE, leads to thymic atrophy [45,[67][68][69][70][71]. Our research in DA rats immunized for EAE [45] linked this phenomenon to the disease-induced rise in the circulating levels of interleukin (IL)− 6 and tumor necrosis factor (TNF)-α, the cytokines causally linked with thymic atrophy [72][73][74].…”
Section: Thymic Involutionmentioning
confidence: 84%
See 2 more Smart Citations